KKN TEMATIK: PENINGKATAN KUALITAS HIDUP BERSIH DAN SEHAT MASYARAKAT DESA LAPAO-PAO KABUPATEN KOLAKA - Farman Farman; Chairuddin Chairuddin; Herlina Herlina; Marniati Marniati; Fitriyani Hali; Akbar Nasrum (LPPM STAIMAS WONOGIRI, 2021)
Maintaining cleanliness and health is something that should be done for the community because it will have an impact on the quality of life of the community. Lapao-pao Village community awareness of the cleanliness of the surrounding environment is still low. This is indicated by the fact that there is still a lot of garbage piled up in several places and on the roadside and there is still some garbage scattered around the river in Lapao-pao Village. Therefore, it is necessary to carry out community empowerment activities on the cleanliness and health of the Lapao-pao Village community. The purpose of this activity is to increase public understanding about a clean environment and be able to encourage people to empower themselves consciously and sustainably to create a clean and healthy environment in the midst of the COVID-19 pandemic. The implementation of activities to improve the quality of clean and healthy life for the Lapao-pao Village community through the Community Service Program is carried out with steps consisting of preparation, implementation and evaluation of activities. The programs that will be implemented in this activity are the manufacture of trash cans, cleaning of the Langonde River tourist attractions, the manufacture of park chairs for the Langonde River tourist attractions, mosque clean operations and mutual assistance in cleaning the village. The planned activities have been realized with outputs in the form of trash cans, park chairs, clean community residential environments, clean mosques and clean rivers. With this activity, it is hoped that the Lapao-pao Village community can foster a more caring attitude and develop themselves in an effort to maintain the cleanliness and health of the community environment. The improved quality of clean and healthy life of the Lapao-pao Village community will have an impact on other village communities.